Basic Transport Phenomena in Biomedical Engineering - Fournier, Ronald L. (London : Taylor and Francis, 2017)
"This will be a substantial revision of a good selling text for upper division/first graduate courses in biomedical transport phenomena, offered in many departments of biomedical and chemical engineering. Each chapter will be updated accordingly, with new problems and examples incorporated where appropriate. A particular emphasis will be on new information related to tissue engineering and organ regeneration. A key new feature will be the inclusion of complete solutions within the body of the text, rather than in a separate solutions manual. Also, Matlab will be incorporated for the first time with this Fourth Edition."--Provided by publisher.
Chapter 1 Introduction -- chapter 2 A review of thermodynamic concepts -- chapter 3 Physical properties of the body fluids and the cell membrane -- chapter 4 The physical and flow properties of blood and other fluids -- chapter 5 Mass transfer fundamentals -- chapter 6 Mass transfer in heterogeneous materials -- chapter 7 Oxygen transport in biological systems -- chapter 8 Pharmacokinetic analysis -- chapter 9 Extracorporeal devices -- chapter 10 Tissue engineering and regenerative medicine -- chapter 11 Bioartificial organs.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING -- Mechanical; Biological transport; Biomedical engineering; Biotechnology